The The Influence of Google Ads Campaigns and Digital Marketing Content Strategy on Sales Conversion Rates: at PT XXX - Ardaman Syaputra; Hariandy Hasbi (Dinasti Publisher, 2024)
Tight business competition requires companies to implement various strategies in order to increase sales conversions. The aim of this research is to evaluate the influence of Google Ads campaigns and digital marketing content strategies on sales conversion rates at PT XXX. This research uses quantitative research methods with a survey approach. Research data was collected from questionnaires. The data analysis technique used in this research is regression testing using the SPSS program. The research results show that there is a positive interactive influence between the Google Ads campaign and digital marketing content strategy on the sales conversion rate at PT XXX with a significance value of 0.00 < 0.05. Therefore, it is recommended for companies to optimize the interaction between Google Ads campaigns and digital marketing content strategies.